Frequency of Fetal and Maternal Complications after C-Section in Vaginal Deliver - Shahneela Memon, Naseem, Hafiza Khatoon, Durga Devi, Kanta Bai, Muhammad Anique, Kiran Aamir, Aamir Ramzan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to evaluate the foetal and mother outcomes of attempting a vaginal delivery following a prior caesarean section. Study Design: Cross-sectional study Place and Duration: Gynaecology and Obstetrics Department Ghulam Mohammad Maher Medical College Sukker. January 2022-December 2022 Methods: Total 50 pregnant females had gestational age 37-42 weeks and had history of one c-section were included. During labor, the mother and baby were closely monitored for indicators of fetal distress, including changes in heart rate, discomfort, and tenderness in the lower abdomen. Written informed consent was obtained using a consent form, and data was collected using pre-designed Performa. Complications among all females were recorded. SPSS 23.0 was used to analyze all data. Results: There were 30 (60%) females had age 18-30 years, 16 (32%) patients had age 31-40 years and 4 (8%) had age 41-45 years. Mean gestational age of the females was 39.17±14.63 weeks. Majority 35 (70%) females had poor socioeconomic status. 21 (42%) cases were educated. Out of the 50 pregnant females, 16 (32%) had vaginal deliveries and 34 (68%) had emergency cesarean section. Frequency of fetal distress was higher in cases of c-section as compared to vaginal deliveries with p value <0.005. As per maternal complications, wound infection and post op fever was higher in c-section while perineal tear and UTI was higher in vaginal deliveries. Post-partum hemorrhage was found in 7 cases, cases in c-section and 3 cases in vaginal deliveries. Frequency of feto-maternal favorable outcomes in vaginal deliveries were higher but difference was insignificant. Conclusion: This research shows that CS is associated with a higher risk of fetal distress, wound infection, and mother fever than vaginal delivery. Future morbidity from CS can be reduced if pregnant patients are urged to have vaginal births. Keywords: C-sectional, vaginal delivery, Complications, Favorable outcomes